Analysis Of Plot And Suspense Structures In “Abandoned By Disney” Creepypasta Using Noël Carroll’s Theory - Rini Susriyani; Andy Endra Krisna (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
The rise of the internet horror can be found online, in particular as a type of stories called the “creepypasta”. There seems to be a few studies on creepypasta that focus on the narrative structure. An American philosopher Noël Carroll who explains the structure of horror narratives and how it can be used to produce the desired horror effect. The theory used in this research is the plot structure and suspense as stated by Carroll. The central question of this research is how to explain the structures of plot and suspense in a creepypasta story, in light of Carroll’s theory. The creepypasta selected for this study is “Abandoned by Disney” by Christopher Howard Wolf. The analysis is conducted using qualitative content analysis method. The findings show that the plot structure corresponds to Carroll’s complex-discovery plot, with a longer onset stage, where the story’s monster is foreshadowed, and a shorter discovery stage, where the monster is revealed. The suspense, in the form of story questions generated in the reader, corresponds to the plot stages; the longer onset stage generates more questions to sustain suspense, and the discovery stage generates fewer questions as the monster is revealed.